2022
DOI: 10.1155/2022/1862911
|View full text |Cite|
|
Sign up to set email alerts
|

Design and Simulation of Logistics Network Model Based on Particle Swarm Optimization Algorithm

Abstract: With the continuous development of e-commerce, logistics and express services have penetrated into every aspect of people’s life. Research on the optimization of logistics network model is helpful to reduce the waste of routes, improve the utilization rate of transportation tools and hubs, and thus reduce the organizational cost of logistics. In this paper, the basic model of hub-and-spoke network (HSN) is constructed based on the principle of minimizing the connection distance and total cost between hubs. By … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…The DL approach [41] is set as a convolutional neural network with eight nodes in the input layer, eight nodes in every immediate layer and eight output nodes in the output layer. As we can see from Figure 7, in solving the logistics network robustness problem, the proposed APS system can obtain a solving performance similar to those of artificial intelligence algorithms, such as the ACO [36], ANN [37,38], PSO [13,39,40], GA [39] and DL [41]. When the number of logistics nodes is small, such as 30 nodes in Figure 7a and 60 nodes in Figure 7b, these artificial intelligence algorithms can obtain a similar performance, where the proposed APS can obtain satisfying computing errors.…”
Section: Comparison and Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…The DL approach [41] is set as a convolutional neural network with eight nodes in the input layer, eight nodes in every immediate layer and eight output nodes in the output layer. As we can see from Figure 7, in solving the logistics network robustness problem, the proposed APS system can obtain a solving performance similar to those of artificial intelligence algorithms, such as the ACO [36], ANN [37,38], PSO [13,39,40], GA [39] and DL [41]. When the number of logistics nodes is small, such as 30 nodes in Figure 7a and 60 nodes in Figure 7b, these artificial intelligence algorithms can obtain a similar performance, where the proposed APS can obtain satisfying computing errors.…”
Section: Comparison and Discussionmentioning
confidence: 81%
“…More importantly, the problem-solving process of our proposed artificial system is greatly simplified, where the complex biological instruments and professional biological operations [14,15,42,43] have all disappeared in our method, such as the Physarum cultivation, environmental control, experimental design, biosafety and data analysis. Now, the related artificial intelligence algorithms are listed here for a comparison to solve the traffic planning problem of Mexican highways, including the ant colony optimization (ACO) [36], artificial neural network (ANN) [37,38], particle swarm optimization (PSO) [13,39,40], genetic algorithm (GA) [39] and deep learning (DL) approach [41]. The related results are shown in Figure 7a-d, where the number of network nodes is extended from 30, 60, 90 to 120.…”
Section: Comparison and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%